Neurocysticercosis and HIV/AIDS co‐infection: A scoping review. Issue 10 (23rd August 2021) - Jewell, Paul D.; Abraham, Annette; Schmidt, Veronika; Buell, Kevin G.; Bustos, Javier A.; Garcia, Hector H.; Dixon, Matthew A.; Walker, Martin; Ngowi, Bernard J.; Basáñez, Maria‐Gloria; Winkler, Andrea S.
Abstract: Objectives: Neurocysticercosis (NCC) and human immunodeficiency virus (HIV) have a high disease burden and are prevalent in overlapping low‐ and middle‐income areas. Yet, treatment guidance for people living with HIV/AIDS (PLWH/A) co‐infected with NCC is currently lacking. This study aims to scope the available literature on HIV/AIDS and NCC co‐infection, focusing on epidemiology, clinical characteristics, diagnostics and treatment outcomes. Methods: The scoping literature review methodological framework, and the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines were followed. A total of 16, 969 records identified through database searching, and 45 additional records from other sources were reduced to 52 included studies after a standardised selection process. Results: Two experimental studies, ten observational studies, 23 case series/case reports and 17 reviews or letters were identified. Observational studies demonstrated similar NCC seroprevalence in PLWH/A and their HIV‐negative counterparts. Of 29 PLWH/A and NCC co‐infection, 17 (59%) suffered from epileptic seizures, 15 (52%) from headaches and 15 (52%) had focal neurological deficits. Eighteen (62%) had viable vesicular cysts, and six (21%) had calcified cysts. Fifteen (52%) were treated with albendazole, of which 11 (73%) responded well to treatment. Five individuals potentially demonstrated an immune‐reconstitution inflammatory syndrome after commencing antiretroviral therapy, although this was in the absence of immunological and neuroimaging confirmation. Conclusions: There is a paucity of evidence to guide treatment of PLWH/A and NCC co‐infection. There is a pressing need for high‐quality studies in this patient group to appropriately inform diagnostic and management guidelines for HIV‐positive patients with NCC.